2007
DOI: 10.1103/physrevlett.99.154102
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Noise from Chaos

Abstract: Chaotic systems share with stochastic processes several properties that make them almost undistinguishable. In this communication we introduce a representation space, to be called the complexity-entropy causality plane. Its horizontal and vertical axis are suitable functionals of the pertinent probability distribution, namely, the entropy of the system and an appropriate statistical complexity measure, respectively. These two functionals are evaluated using the Bandt-Pompe recipe to assign a probability distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
647
1
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(677 citation statements)
references
References 23 publications
14
647
1
15
Order By: Relevance
“…On the contrary, the value of C increases for increasing τ in the range τ = 2..80 ns, reaches a maximum at τ = 80 ns, and decreases for longer τ . Previous works have shown that the correlations present in deterministic chaotic systems typically yield intermediate values of H ranging from 0.45 to 0.75 and values of C near the maximum, which is C = 0.5 for D = 6 [8]. This means that correlated dynamics is found to dominate in the range τ = 14..120 ns in our experimental realization.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…On the contrary, the value of C increases for increasing τ in the range τ = 2..80 ns, reaches a maximum at τ = 80 ns, and decreases for longer τ . Previous works have shown that the correlations present in deterministic chaotic systems typically yield intermediate values of H ranging from 0.45 to 0.75 and values of C near the maximum, which is C = 0.5 for D = 6 [8]. This means that correlated dynamics is found to dominate in the range τ = 14..120 ns in our experimental realization.…”
supporting
confidence: 49%
“…To distinguish between these two components we propose, in this letter, to use quantifiers derived from information theory. In particular, permutation entropy and statistical complexity [8] are good candidates for this task. They have already shown to be successful in identifying the internal structures of time series originated from delay systems [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally proposed and assessed for one-dimensional signals, for which it was shown to be able to detect transition points between different regimes [18]. This feature is the product of an entropy and a stochastic distance between the model which best describes the data and an equilibrium distribution [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Complexity measures have been shown to be powerful tools for detecting dynamical changes in time series from epileptic patients [27] and in speech signals [20,28], for distinguishing chaotic signals from stochastic ones, for distinguishing among different degrees of stochasticity [29], for quantifying stochastic and coherence resonances [30], and for classifying spatio-temporal patterns [31,32] and neural networks [33,34] etc.…”
Section: Introductionmentioning
confidence: 99%